The role of -omics technology in the pathophysiology, diagnosis, and treatment of cardiovascular diseases - Ümit Yaşar Sinan; Serkan Unlu (KARE Publishing, 2017)
Although evident improvement has occurred in the diagnosis and treatment of cardiovascular disease (CVD), it is still the most important cause of mortality worldwide. The majority of the CVDs are multifactorial and polygenic. Therefore, it is logical to use genomics, proteomics, lipidomics, and metabolomics together for diagnosis and effective treatment of CVD. 'Genome' is the combination of the words 'gene' and 'chromosome,' and includes all protein-coding genes and intergenic spaces (as well as intragenic regions, or introns, within genes) in an organism. Proteins that are synthesized in a cell, tissue, or organism are all called proteomes. Proteomics is the study of proteomes. The analysis of the lipodome, or all lipids synthesized in the organism, as well as lipid-derived mediators, and the functions of these mediators in biological systems, is the field of lipidomics. The metabolome is the complete set of low-molecular-weight metabolites and molecules in a human or any living organism. Metabolomic is the systematic analysis of small molecules and metabolites in human or animal biological fluids. The number of biomarkers used for the purpose of evaluating the risk of cardiovascular events is very limited and many of them are old. The drugs that were produced 30 years ago are still used in treatment. Development of -omics science plays an important role in the search for new biological markers that can be used in the diagnosis of CVD and there is a growing need for advancement of these branches of genetics. The recognition and internalization of -omics by clinicians is a time-consuming process, but will be more important in the near future.